Global, regional, and national burden of atrial fibrillation and flutter associated with metabolic risk factors, 1990–2021 - Wang, Lu; Qin, Xinghua; Jin, Linyan; Gong, Haoyu; Gao, Chong; Wang, Hongtao; Liu, Peng (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesAtrial fibrillation/flutter (AF/AFL) is increasingly correlated with metabolic risk factors. This study analyzed mortality, disability-adjusted life years (DALYs), annual percentage changes (APCs), and estimated annual percentage changes (EAPCs), stratified by age, sex, Socio-demographic Index (SDI), and region, to evaluate the global burden of AF/AFL linked to metabolic risk factors.MethodsData on prevalence, incidence, mortality, DALYs, and age-standardized rates (ASRs) for AF/AFL associated with metabolic risk factors were extracted from the Global Burden of Disease (GBD) 2021 study. EAPCs were used to assess temporal trends in ASRs.ResultsIn 2021, metabolic risk factors were correlated with approximately 117,012 deaths and 2,881,800 DALYs globally due to AF/AFL, reflecting increases of 196.08% and 154.51%, respectively, compared to 1990. The burden varied considerably by sex, SDI, and region. Women, older adults, and high-SDI regions exhibited higher burdens, while men, younger individuals, and low-SDI regions showed more rapid increases.ConclusionsMetabolic risk factors are strongly correlated with the global burden of AF/AFL. Strengthening cost-effective interventions targeting these modifiable risks is essential—particularly in regions facing high or rapidly growing burdens.